Effects of Weight Loss on Adipose Tissue, Liver and Heart Metabolism in Humans - Viljanen, Antti (fi=Turun yliopisto|en=University of Turku|, 2009)
Obesity has become the leading cause of many chronic diseases, such as type 2 diabetes and cardiovascular diseases. The prevalence of obesity is high in developed countries and it is also a major cause of the use of health services. Ectopic fat accumulation in organs may lead to metabolic disturbances, such as insulin resistance.Weight loss with very-low-energy diet is known to be safe and efficient. Weight loss improves whole body insulin sensitivity, but its effects on tissue and organ level in vivo are not well known. The aims of the studies were to investigate possible changes of weight loss in glucose and fatty acid uptake and perfusion and fat distribution at tissue and organ level using positron emission tomography and magnetic resonance imaging and spectroscopy in 34 healthy obese subjects. The results showed that whole-body insulin sensitivity increased after weight loss with very-low-energy diet and this is associated with improved skeletal muscle insulin-stimulated glucose uptake, but not with adipose tissue, liver or heart glucose uptake. Liver insulin resistance decreased after weight loss. Liver and heart free fatty acid uptakes decreased concomitantly with liver and heart triglyceride content. Adipose tissue and myocardial perfusion decreased. In conclusion, enhanced skeletal muscle glucose uptake leads to increase in whole-body insulin sensitivity when glucose uptake is preserved in other organs studied. These findings suggest that lipid accumulation found in the liver and the heart in obese subjects without co-morbidies is in part reversible by reduced free fatty acid uptake after weight loss. Reduced lipid accumulation in organs may improve metabolic disturbances, e.g. decrease liver insulin resistance. Keywords: Obesity, weight loss, very-low-energy diet, adipose tissue metabolism, liver metabolism, heart metabolism, positron emission tomography